THE POTENTIAL OF EXTRACT SINGKIL LEAVES (Premna cordifolia Roxb.) AS ANTIBACTERIAL AGENTS AGAINST Propionibacterium acnes - Az-zahra, Deannisa Khoiru; Astuti, Winni; Marliana, Eva (PROSIDING SEMINAR KIMIA, 2023)
One of the causes of acne is infection by the bacteria Propionibacterium acnes. Singkil (Premna cordifolia Roxb.) is a kind of herb plant from Kutai Kartanegara which is used as a traditional herb including for acne’s treatment. This study aims to know the content of secondary metabolites compound in singkil’s extract and determine the antibacterial activity against Propionibacterium acnes KCCM 41747 bacteria. In this study, it’s phytochemical screening and antibacterial activity test using the disc diffusion method on methanol extract, n-hexane, ethyl acetate and water-methanol fractions. the result of phytochemical screening revealed that methanol extract of singkil contains alkaloids, flavonoids, steroids, and saponins. The n-hexane fraction contains steroids and the ethyl acetate fraction contains alkaloids, flavonoids, and phenolics while the water-methanol fraction contains alkaloids, flavonoids, and phenolics. The antibacterial activity test extract with a concentration of 10% showed that the diameter of clear zone of the metanol extract, n-hexane fraction, ethyl acetate fraction, and water-methanol fraction were 13 mm, 9 mm, 13,67 mm and 6 mm, respectively. The ethyl acetate fraction had the highest antibacterial activity among the four extracts. A minimum inhibitory concentration value of the ethyl acetate fraction against Propionibacterium acnes KCCM 41747 was 0,625%. The ethyl acetate fraction have the potential as an antibacterial against the bacteria Propionibacterium acnes KCCM 41747. Keywords: Premna cordifolia Roxb., Secondary metabolites, Propionibacterium acnes KCCM 41747